Self Disclosure Instrument: Instrument Standardization through Rasch Model - Tririzky, Reza; Daharnis, Daharnis; Ardi, Zadrian; Putra, Ade Herdian (Universitas Negeri Padang, 2025)
The understanding of the extent to which humans can express themselves can be one of the efforts in overcoming various problems that humans face that requires a well-standardized tool. The purpose of this study is to standardize the self-disclosure instrument through the Rasch model. Data collection for this study involved 53 research participants from a high school in Bandung City, West Java. The collected data was then processed and analyzed using the Rasch model with the Winstep application. It was found that out of the 24 initial statement items, 4 did not meet the Rasch model testing criteria. The remaining 20 items could be further utilized in the research. This instrument can then be further utilized in tracing and understanding individual self-disclosure that supports the intervention process to increase self-disclosure.